DINAMIKA FIQH DI INDONESIA (Telaah Historis Lahirnya Fiqh Keindonesiaan) (Mazahib, 2007)
The rise of Indonesian-Islamic jurisprudence proposal originates from the concerns that available Islamic jurisprudence has put to much emphasis on Arabian context so that it needs to be localized and contextualized. In general, there are two themes of Islamic law reformation in Indonesia: first, returning to the true message of Koran and Sunnah; second, Indonesiazing existing Islamic jurisprudence. The former is carried out by purifying Islamic rituals from non-Islamic elements, opening the gate of ijtihad, eliminating uncritical obedience to the school of law, allowing eclecticism through comparative study. The latter is conducted, among other things, by making customary law as a source of Islamic law in Indonesia.